2015
DOI: 10.1021/acs.jpcb.5b04614
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oxygen Bridged Manganese Model Complexes Using Multifrequency17O-Hyperfine EPR Spectroscopies and Density Functional Theory

Abstract: Multifrequency pulsed EPR data are reported for a series of oxygen bridged (μ-oxo/μ-hydroxo) bimetallic manganese complexes where the oxygen is labeled with the magnetically active isotope (17)O (I = 5/2). Two synthetic complexes and two biological metallocofactors are examined: a planar bis-μ-oxo bridged complex and a bent, bis-μ-oxo-μ-carboxylato bridge complex; the dimanganese catalase, which catalyzes the dismutation of H2O2 to H2O and O2, and the recently identified manganese/iron cofactor of the R2lox pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 82 publications
2
55
0
Order By: Relevance
“…1 and feature Mn⋯Mn distances ranging from 8.7 to 15.1 Å as controlled by the spacer group of the dicarboxylate. Previously reported dimanganese(III,IV) and dimanganese(II,III) systems have been investigated by HFEPR, [35][36][37] and more importantly, so have dimanganese(III) complexes, such as a μ-oxido complex by Retegan et al, 10 a μ-fluorido complex by Pedersen et al, 8 and a system more relevant to those reported here, namely a dimanganese(III,III) complex without any bridging atoms, but with covalent connections between the two Mn III ions via two trans four-bond π-conjugated O-C-C-C-O pathways. 28 A tetranuclear complex comprising a square grid of Mn III ions linked by Schiff base ligands has also been studied by HFEPR, 38 but this complicated spin system is beyond the present study.…”
Section: Introductionmentioning
confidence: 99%
“…1 and feature Mn⋯Mn distances ranging from 8.7 to 15.1 Å as controlled by the spacer group of the dicarboxylate. Previously reported dimanganese(III,IV) and dimanganese(II,III) systems have been investigated by HFEPR, [35][36][37] and more importantly, so have dimanganese(III) complexes, such as a μ-oxido complex by Retegan et al, 10 a μ-fluorido complex by Pedersen et al, 8 and a system more relevant to those reported here, namely a dimanganese(III,III) complex without any bridging atoms, but with covalent connections between the two Mn III ions via two trans four-bond π-conjugated O-C-C-C-O pathways. 28 A tetranuclear complex comprising a square grid of Mn III ions linked by Schiff base ligands has also been studied by HFEPR, 38 but this complicated spin system is beyond the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The same advantages can be seen for more complex systems. Our laboratories have recently reported high field EDNMR data for a series of oxygen (µ-oxo) bridged manganese homodimers and manganese-iron heterodimers [583]. This set included two simple synthetic complexes and two biological cofactors, from the manganese calatase enzyme and R2-like ligand oxidase (R2lox) enzyme.…”
Section: Ednmr On Transition Metal Containing Systemsmentioning
confidence: 99%
“…At this field range, the Larmor frequency, ν n , of many nuclei is significantly larger than 10 MHz, allowing for their detection by EDNMR. Over the last decade, a series of reports appeared that used high-field EDNMR to characterize a number of chemical systems and materials with a wide variety of nuclei in radical [228,236,545,[557][558][559][560][561][562][563][564] and transition metal containing systems [272,273,275,276,[565][566][567][568][569][570][571][572][573][574][575][576][577][578][579][580][581][582][583][584].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic properties of enzymatic oxygen centers have been most commonly probed indirectly by electron paramagnetic resonance (EPR) and electron nuclear double resonance (ENDOR) spectroscopies [613]. However, direct detection of 17 O centers in catalytic reaction intermediates is rare.…”
Section: Introductionmentioning
confidence: 99%